ASSESSMENT OF MICROBIAL REDUCTION IN CHICKEN EGG SUBJECTED TO DIFFERENT BOILING DURATION - Kyakma, Samson Sukumun; Bathon, Chabiya Atu; Abuh, Nasiru (FUDMA Journal of Sciences, 2026)
The microbial safety of eggs is a major public health concern, particularly in regions where handling and storage conditions may predispose them to contamination. This study evaluated the effect of different boiling durations (3, 5, 10, and 15 minutes) on the microbial load and safety of chicken eggs. Fresh egg samples were subjected to controlled boiling at the specified time intervals, after which microbiological analyses were conducted to determine aerobic plate count (APC) and total coliform count (TCC). Standard biochemical tests were further employed to identify predominant bacterial isolates. Results revealed a progressive reduction in microbial load with increasing boiling time. Eggs boiled for 3 minutes recorded the highest APC and TCC values, indicating insufficient microbial inactivation, while samples boiled for 15 minutes showed the lowest counts, suggesting improved microbial safety. Intermediate reductions were observed at 5 and 10 minutes of boiling. Biochemical characterization identified Staphylococcus spp. and Escherichia coli as the predominant isolates, with their presence markedly reduced at longer boiling durations. The findings demonstrate that boiling time significantly influences the microbial quality of eggs, with longer durations enhancing bacterial reduction and safety. It is therefore recommended that eggs be boiled for at least 10–15 minutes to ensure adequate microbial inactivation and minimize potential health risks. This study provides useful insights for consumers and public health authorities on safe egg preparation practices.
Keywords: Egg; Microbial Safety; Boiling duration; Egg texture and quality; Microbial Contamination